2014
DOI: 10.1111/eea.12181
|View full text |Cite
|
Sign up to set email alerts
|

Rearing history affects behaviour and performance of two virulent Nasonovia ribisnigri populations on two lettuce cultivars

Abstract: Many aphid species have become virulent to host‐plant resistance, which limits the sustainability of insect resistance breeding. However, when this adaptation to resistant plants is associated with fitness costs for the aphids, virulence can be lost in the absence of resistant plants. For two populations of the lettuce aphid, Nasonovia ribisnigri (Mosely) (Hemiptera: Aphididae), we evaluated whether virulence to Nr‐gene‐based resistance was lost on a susceptible lettuce, Lactuca sativa L. (Asteraceae), and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Indeed, aphids continuously adapt their behavior to the plant characteristics, like their resistance level ( Pompon and Pelletier, 2012 ; Jhou et al., 2021 ). Their experience on the plants they are reared on modulates aphids physiology temporarily, like duration of phloem intake, probing frequency, salivation duration ( ten Broeke et al., 2014 ) and the gene expression level of particular effectors related to host utilization ( Eyres et al., 2016 ; Thorpe et al., 2020 ). The second main difference concerns the number of repressed DEGs in the infested resistant line: Niu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, aphids continuously adapt their behavior to the plant characteristics, like their resistance level ( Pompon and Pelletier, 2012 ; Jhou et al., 2021 ). Their experience on the plants they are reared on modulates aphids physiology temporarily, like duration of phloem intake, probing frequency, salivation duration ( ten Broeke et al., 2014 ) and the gene expression level of particular effectors related to host utilization ( Eyres et al., 2016 ; Thorpe et al., 2020 ). The second main difference concerns the number of repressed DEGs in the infested resistant line: Niu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Where the same resistant plant was reported in multiple studies, for example the Nasonovia ribisnigri resistant lettuce variety Corbana 59 , 60 and the Rhopalosiphum padi resistant wild relative of barley Hsp5 21 , 61 , data were extracted from the study with the fewest contrasting experimental variables or, if all studies were similar in their design, the study that reported the greatest number of EPG variables. Studies often presented results on the feeding behaviour of multiple insect species for the same plant type 29 .…”
Section: Methodsmentioning
confidence: 99%
“…Where the same resistant plant was reported in multiple studies, for example the Aphis craccivora resistant IVC-12 cowpea line 25,26 , the Nasonovia ribisnigri resistant lettuce variety Corbana 60,61 , and the Rhopalosiphum padi resistant wild relative of barley Hsp5 31,62 , data were extracted from the study with the fewest contrasting experimental variables or, if all studies were similar in their design, the study that reported the greatest number of EPG variables. Studies often presented results on the feeding behaviour of multiple insect species for the same plant type 63 .…”
Section: Data Extractionmentioning
confidence: 99%